1990
DOI: 10.1007/bf01745219
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of two isoforms of calsequestrin in rabbit slow-twitch muscle

Abstract: The cardiac and fast-twitch skeletal muscle forms of the Ca2(+)-binding protein calsequestrin (CS) are the products of two different genes, both of which are transcribed in slow-twitch skeletal muscle, though at much different rates (Scott et al., 1988., Fliegel et al., 1989). We have investigated this problem more closely at the protein level, on isolated terminal cisternae (TC) of the sarcoplasmic reticulum (SR) of rabbit slow-twitch muscle, and following purification of two distinct forms of CS from whole t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…CSQ purification from canine skeletal muscle led to isolation of both CSQ isoforms, with the fast-twitch form (63 kDa) being the predominant one, as previously reported (38). Application of our phosphatase/CK2 kinase assay to the skeletal muscle preparation showed that, as in heart tissue, cardiac CSQ (55 kDa) was present mainly as the phosphoprotein (Fig.…”
Section: Resultssupporting
confidence: 73%
“…CSQ purification from canine skeletal muscle led to isolation of both CSQ isoforms, with the fast-twitch form (63 kDa) being the predominant one, as previously reported (38). Application of our phosphatase/CK2 kinase assay to the skeletal muscle preparation showed that, as in heart tissue, cardiac CSQ (55 kDa) was present mainly as the phosphoprotein (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Terminal cisternae are enriched in the content of both skeletal and cardiac isoforms of CS (Damiani et al, 1990) and were used as positive controls in immunoblot experiments with polyclonal antibodies to animal CS.…”
Section: Preparative Proceduresmentioning
confidence: 99%
“…Phenyl-Sepharose (Pharmacia) column chromatography was carried out using either the procedure described by Heilmann et al (1993) for purification of CR from human liver (procedure 1) or that described by Damiani et al (1990) for purification of CS from rabbit skeletal muscle (procedure 2).…”
Section: Phenyl-sepharose Chromatographymentioning
confidence: 99%
See 2 more Smart Citations